2018
DOI: 10.1177/1035304618758941
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth, welfare models and inequality in the context of globalisation

Abstract: The recent economic crisis was a test case for many advanced countries to determine the capacity of their socio-economic model to cope with the challenges of globalisation and financial crash. From this perspective, the aim of this article is to explore whether the expansion of the welfare state should be seen as a barrier to economic growth and competitiveness, as ‘neoliberal’ economists often argue, or whether increasing public social provision might contribute to enhancing real income. After a comparative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 53 publications
2
18
0
1
Order By: Relevance
“…A similar result was obtained by Butcher et al (2012) and by Tridico and Paternesi Meloni (2018) who found that minimum wages have an impact on wage inequality, particularly in the United Kingdom and the United States during the 1990s and 2000s.…”
Section: Individualized Employment Relations At Organizational Levelsupporting
confidence: 85%
“…A similar result was obtained by Butcher et al (2012) and by Tridico and Paternesi Meloni (2018) who found that minimum wages have an impact on wage inequality, particularly in the United Kingdom and the United States during the 1990s and 2000s.…”
Section: Individualized Employment Relations At Organizational Levelsupporting
confidence: 85%
“…Generally speaking, it can be argued that since export-led mercantilist countries experienced redistribution at the expense of labour and low income households, this has led to low domestic demand dynamics and rising external competitiveness. However, falling wage shares did not foster personal income inequality to the same degree in all countries, since it has remained lower in Scandinavian and Continental European countries compared to other welfare models (Tridico and Paternesi Meloni 2018). Furthermore, in these models the redistribution had little relative income effects on consumption.…”
Section: Demand Regimes and Welfare Modelsmentioning
confidence: 79%
“…Since globalisation and financialisation contribute to increasing income inequality, according to the 'compensation thesis', welfare states are maintained to mitigate vulnerability. In this perspective, governments maintain welfare support in order to compensate those who are damaged by such pressures, which will then through several channels even stabilise economic development (Brady et al 2005;Rodrik 1998;Swank 2002;Tridico and Paternesi Meloni 2018). On the contrary, countries belonging to Anglo-Saxon/Liberal, Mediterranean, and partly also the CEEC model opted for lower levels of welfare, following the so-called 'efficiency thesis'.…”
Section: Demand Regimes and Welfare Modelsmentioning
confidence: 99%
“…Tridico and Meloni examine the challenges of economic growth in the context of globalisation and the GFC for developed countries. They argue that state social spending is not, as neo-liberals would have it, a drain on competitiveness and an obstacle to economic efficiency, but that such state expenditures can stimulate growth alongside reducing inequality (Tridico and Meloni, 2018).…”
Section: Introductionmentioning
confidence: 99%